Design, synthesis and biological evaluation of novel benzocoumarin derivatives as potent inhibitors of MAO-B activity - MELETLİ, FURKAN; DEMİR, SERAP; DANIŞ, ÖZKAN (My University, 2024)
The continued research of novel reversible inhibitors targeting monoamine oxidase (MAO) B remains crucial for effectively symptomatic treatment of Parkinson\"s disease. In this study we synthesized and evaluated a new series of 3-aryl benzo[g] and benzo[h] coumarin derivatives as MAO-B inhibitors. Compound A6 has been found to display the most potent inhibitory activity and selectivity against the MAO-B isoform (IC50 = 13 nM and SI = >7693.31 respectively). Inhibition mode of A6 on MAO-B was predicted as mixed reversible inhibition with a Ki value of 3.274 nM. Furthermore, in order to elaborate structure–activity relationships, the binding mode of A6 was investigated by molecular docking simulations.
Keywords: Tıp; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Biyoinorganik Kimya; Sağlık Bilimleri; Temel Bilimler; Medicine; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Bioinorganic Chemistry; Health Sciences; Natural Sciences; Klinik Tıp (Med); Temel Bilimler (Sci); Yaşam Bilimleri (Life); Klinik Tıp; Moleküler Biyoloji Ve Genetik; Mikrobiyoloji; Tropikal Tıp; Kimya Organik; Biyokimya Ve Moleküler Biyoloji; Biyoteknoloji Ve Uygulamalı Mikrobiyoloji; Clinical Medicine (Med); Natural Sciences (Sci); Life Sciences (Life); Clinical Medicine; Molecular Biology & Genetics; Microbiology; Tropical Medicine; Chemistry Organic; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology; Moleküler Tıp; Moleküler Biyoloji; Farmasötik bilim; İlaç Keşfi; Klinik Biyokimya; Organik Kimya; Fizik Bilimleri; Molecular Medicine; Molecular Biology; Pharmaceutical Science; Drug Discovery; Clinical Biochemistry; Organic Chemistry; Physical Sciences; Benzo[g]coumarin; Benzo[h]coumarin; Molecular docking; Monoamine oxidase; Parkinson's Disease